Herbal Medicines for Idiopathic Male Infertility: A Systematic Review - Ahmadian, Mohammad; Salari, Roshanak; Noras, Mohammad R.; Bahrami-Taghanaki, Hamid Reza (Current Drug Discovery Technologies, 2022)
Background: Various medications, surgeries, and assisted reproductive techniques are used to treat male infertility, but the high cost and low effectiveness have made these methods unpopular. The use of herbal medicines such as Withania somnifera, Ceratonia siliqua, Nigella sativa and Alpinia officinarum for the treatment of male infertility has become highly popular in recent years. Objective: We conducted this systematic review to evaluate the recent scientific evidence regarding herbal medicines used to treat idiopathic male infertility (IMI). Methods: Online literature resources were checked using different search engines, including ISI, Web of Knowledge, Medline, PubMed, Scopus, and Google Scholar. Date restrictions were applied to 2020, and the publication language was restricted to English and Persian. The risk of bias was evaluated using the Cochrane method. Results: Out of 851 articles, 14 trials with 1218 participants were included. Of the 15 plants and medicinal products introduced in the selected studies, 12 cases were effective in treating male infertility. Each of these plants or products affects specific components of male fertility for which various mechanisms were mentioned, but most of them had antioxidant effects. No serious side effects were reported. Conclusion: Whitania somnifera roots, Alpinia officinarum, Nigella sativa seeds, Tomato, and Ceratonia siliqua and the formulation of Xperm, PHF, Churna Ratnam, Svaguptadi Churna, Y virilin capsule, manix capsule, and Tradafertil tablet revealed successful outcomes in treatment of idiopathic male infertility.
Keywords: male sterility